Adverse effects of removable orthodontic aligners: A systematic review with single-arm meta-analysis - Cintia Ronchi Lemos; Marianella Aguilar Ventura Fadel; Helena Polmann; Júlia Meller Dias de Oliveira; Patrícia Pauletto; Cristine Miron Stefani; Carlos Flores-Mir; Graziela De Luca Canto (PLoS ONE, 2026)
Background Removable orthodontic aligners are widely used due to their aesthetic appeal, removability, and perceived comfort. However, evidence regarding their potential adverse effects remains limited. Objective To identify and synthesize the adverse effects associated with removable orthodontic aligner therapy. Methods This systematic review with single-arm meta-analysis evaluated adverse effects related to removable orthodontic aligner therapy. Seven electronic databases (Cochrane, Embase, LILACS, Livivo, MEDLINE, Scopus, and Web of Science) and gray literature sources (ProQuest Dissertations and Google Scholar) were searched without language or date restrictions. Two calibrated reviewers independently selected studies. Risk of bias was assessed using RoB 2 for randomized trials and ROBINS-I for non-randomized studies. Due to clinical and methodological heterogeneity, most outcomes were synthesized narratively; meta-analyses were conducted only for pain/discomfort, apical root resorption, and plaque. Results Thirty-four studies met the inclusion criteria, including 10 randomized controlled trials, 6 non-randomized clinical studies, and 18 cohort studies. Randomized trials were predominantly at low risk of bias, whereas most non-randomized and cohort studies were at moderate to high risk. Pain and apical root resorption were the most frequently reported adverse effects. Pain peaked within 24 hours, decreased by day 3, and was minimal by 1 week. Apical root resorption was generally small, with a mean linear loss of −0.33 mm (95% CI −0.55 to −0.11) and a volumetric loss of −4.37 mm³ (95% CI −5.51 to −3.24). Findings on plaque at 3 months were inconclusive. Other reported outcomes included periodontal changes, enamel demineralization, white spot lesions, speech alterations, halitosis, open gingival embrasures, temporomandibular symptoms, and awake bruxism. Conclusion Short-term pain and minor apical root resorption appear to be the most frequently reported adverse effects of removable orthodontic aligners, although the certainty of evidence varies across outcomes. Speech alterations, discomfort, and white spot lesions have also been reported.